2020
DOI: 10.1002/jcp.30002
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of Astragaloside IV on neurite outgrowth via talin‐dependent integrin signaling and microfilament force

Abstract: Integrin plays a prominent role in neurite outgrowth by transmitting both mechanical and chemical signals. Integrin expression is closely associated with Astragaloside IV (AS-IV), the main component extracted from Astragali radix, which has a positive effect on neural-protection. However, the relationship between AS-IV and neurite outgrowth has not been studied exhaustively to date. The present study investigated the underlying mechanism of AS-IV on neurite outgrowth. Longer neurites have been observed in SH-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Furthermore, cells in the Ast10 group were flatter and had elongated spindles at day 1 as compared to the rest of the groups, thus indicating that the microenvironment was more favorable to RSCs. In addition, the RSCs cultured on the conduits with Ast stimulation showed longer axons and more spindle cells, which proved the positive influence of Ast stimulation on neuronal cell proliferation [31]. These data indicated that the addition of Ast can promote cellular adhesion and proliferation and can be used as a neurogenic factor in future nerve-regeneration-related studies.…”
Section: Characterization Of Ast-containing Pu Conduitsmentioning
confidence: 62%
“…Furthermore, cells in the Ast10 group were flatter and had elongated spindles at day 1 as compared to the rest of the groups, thus indicating that the microenvironment was more favorable to RSCs. In addition, the RSCs cultured on the conduits with Ast stimulation showed longer axons and more spindle cells, which proved the positive influence of Ast stimulation on neuronal cell proliferation [31]. These data indicated that the addition of Ast can promote cellular adhesion and proliferation and can be used as a neurogenic factor in future nerve-regeneration-related studies.…”
Section: Characterization Of Ast-containing Pu Conduitsmentioning
confidence: 62%
“…The pathogenesis of RA is extremely complex and involves environmental, immune, genetic and other factors ( 35 , 36 ), thus rendering the achievement of RA targeted treatment development a difficult research target. Currently, increasing attention has been paid to the role of natural herbal extracts with a probable therapeutic effect on the treatment of several diseases, including RA ( 37 , 38 ). For example, Astragalus membranaceus , Tripterygium wilfordii and Radix Paeoniae Alba have been proven to have certain therapeutic effects on RA ( 39 - 41 ).…”
Section: Discussionmentioning
confidence: 99%